Present status of Sicariidae (Arachnida: Araneae) in the Afrotropical region - Lotz, L. N. (Zootaxa, 2012)
In this paper the present state of knowledge of the family Sicariidae in the Afrotropical region is discussed. The Sicariidaein the Afrotropical region, as it stands at present, consists of two genera, viz. Sicarius Walckenaer, 1847 (subfamilySicariinae) with six species: S. albospinosus Purcell, 1908, S. damarensis Lawrence, 1928, S. dolichocephalus Lawrence,1928, S. hahni (Karsch, 1878), S. spatulatus Pocock, 1900, and S. testaceus Purcell, 1908 and Loxosceles Heineken &Lowe, 1835 (subfamily Loxoscelinae) with 13 species: L. fontainei Millot, 1941, L. foutadjalloni Millot, 1941, L. lacroixiMillot, 1941, L. meruensis Tullgren, 1910, L. neuvillei Simon, 1909, L. pallidecolorata (Strand, 1906), L. parramiNewlands, 1981, L. rufecens (Dufour, 1820), L. smithi Simon, 1897, L. speluncarum Simon, 1893, L. spinulosa Purcell,1904, L. valida Lawrence, 1964 and L. vonwredei Newlands, 1980. Loxosceles parrami Newlands, 1981 is here renamedto L. parramae (Newlands, 1981), as it was named for a Miss Parram. Loxosceles valida Lawrence, 1964 is heretransferred to the genus Drymusa Simon, 1893 (Drymusidae) and three species of Loxosceles is revalidated (L. bergeri Strand, 1906, L. pilosa Purcell, 1908 and L. simillima Lawrence, 1927).